2011
DOI: 10.5414/cn107208
|View full text |Cite
|
Sign up to set email alerts
|

Reduced pre-pregnancy proteinuria is associated with improving postnatal maternal renal outcomes in IgA nephropathy women

Abstract: Aims: In patients with immunoglobulin A (IgA) nephropathy, postnatal renal outcomes vary depending on kidney function and proteinuria. However, whether a decrease in proteinuria prior to conception improves postnatal maternal renal outcomes is unknown. Methods: This was a single-center retrospective study. A total of 52 pregnant women with biopsy-proven IgA nephropathy was enrolled in the study between January 2004 and December 2009. We collected data on proteinuria, which had been measured 1 year prior to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The group with eGFR <45 mL/min showed deterioration in the eGFR after five years even without pregnancy as a natural course. On the other hand, proteinuria was previously demonstrated to be significantly associated with the deterioration of postnatal maternal outcomes (25). Youxia et al reported that proteinuria during pregnancy is a predictor of adverse pregnancy outcomes (26).…”
Section: Discussionmentioning
confidence: 99%
“…The group with eGFR <45 mL/min showed deterioration in the eGFR after five years even without pregnancy as a natural course. On the other hand, proteinuria was previously demonstrated to be significantly associated with the deterioration of postnatal maternal outcomes (25). Youxia et al reported that proteinuria during pregnancy is a predictor of adverse pregnancy outcomes (26).…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Other diseases such as IgA or reflux nephropathy usually display a good prognosis, at least in the presence of normal kidney function. [17][18][19][20][21][22][23] Despite rising interest, few large cohorts of nonselected patients with CKD encompassing the most frequently encountered disorders in clinical practice are available.…”
mentioning
confidence: 99%
“…The main characteristics of the case series are reported in Table 1 , Table 2 , Table 3 and Table 4 [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%